Studying the Effect of Laminating Pressure, Temperature and Time on the Adhesion Between Interlining and Felt Fabric. - Hoang, Thanh Thao; Nguyen, Minh Tuan; Nguyen, Thi Thu Ha (Old Journal, 2018)
Technological parameters of interlined fabrics such as laminating pressure, temperature, and time greatly affects the aesthetics of felt suits. This paper studies the effects of the following laminating modes: laminating pressure: 2.8, 2.9, 3.0, 3.1, 3.2 bar/cm2, laminating temperature: 140, 145, 150, 155, 160 °C, laminating time: 18, 19, 20, 21, 22 seconds to the bond strength between Furgood interlining and two types of woven felt fabric: D1 (45.6% Polyester + 27.1 % Wool + 11% Visco + 16.3% Acrylic) and D2 (25.3% Cotton + 74.7% Polyester) - these are commonly used for felt clothing. From those, we can find out the relation between bond strength and laminating pressure, temperature, and time. The research results can help choosing suitable parameters to avoid frequent problems, like blistering, glossy surface fabric, mex stick to the right surface of the fabric,... ensuring the aesthetics of fabrics for felt suit.